0219 Undergraduate Human Factors In Healthcare Questionnaire: Assessing Necessity And Demand For Human Factor Exposure Of Undergraduate Healthcare Professionals In Hull And The East Riding Of Yorkshire. (1st November 2014) - Gopal, Alan; Purva, Makani
Abstract : Background and context: Expertise, competence and hard work alone are an incomplete defence against human error, the biggest contributor to unintentional harm in healthcare. 1 Human factors 2 study how human interactions, error chains and system failures compound each other to cause adverse patient outcomes, 1 and guides implementation of suitable safeguards against error. This movement has the backing of the Nursing and Midwifery Council (NMC) 3 and the General Medical Council (GMC). 4 They have signed the National Quality Board Concordat 5, 6 in acknowledgement of the advantages of integrating human factors principles and practice into core undergraduate and postgraduate curricula for healthcare-professionals. 7 There are relatively few efforts to effectively convert the knowledge of changes in patient safety into non-technical skills beyond the undergraduate classroom aside from highly supervised and restricted clinical involvement. 7 Few undergraduates have received enough exposure to clearly defined human factors theory or practice to demonstrate a working knowledge of this key field of study. Methodology: We have piloted an online Human Factors questionnaire which is to be circulated to undergraduate nurses and doctors across the region to explore the recognition, understanding and level of training in human factors at the undergraduate level. This questionnaire incorporates aspects of the Safety Attitudes Questionnaire 8 to assess insight and opinion of healthcare culture, particularly teamwork and safety climates. Anticipated outcome: We anticipate that this survey will highlight a need and demand for undergraduate education and training in human factors throughout the region, and will highlight key areas to address. We intend to deploy this questionnaire and present the results at the conference. Potential impact: This study will indicate the viability and potential value of further projects pertaining to undergraduate human factors. The results will be used to guide the design, development and deployment of human factor education and training at the undergraduate level within the region. References: Vincent C, Neale G, & Woloshynowych M. BMJ, 2001;322:517–519 Leonard M, Graham S, & Bonacum D. Qual Saf Health Care, 2004;13:i85–i90 Nursing and Midwifery Council. (NMC). (2008). The Code - Standards of Conduct, Performance and Ethics. London, NMC General Medical Council. (GMC). (2006). Good Medical Practice. London, GMC NMC and GMC. (2012). Joint Statement of Professional Values. London National Quality Board, . (2013). Human Factors in Healthcare: A Concordat from the National Quality Board. London, NHS England Paterson-Brown S. BMJ 2011;342:d214 Sexton JB, Helmreich RL, et al . BMC Health Services Research 2006;6:44